TARGETING MULTIPLE PATHWAYS WITH ONE MOLECULE: THE THERAPEUTIC VERSATILITY OF TIRZEPATIDE - Patrycja Jędrzejewska-Rzezak; Adam Żuczek; Kinga Dyndał; Marcelina Broda; Olga Żuczek; Katarzyna Urbańska; Izabela Szczap; Anna Hawryluk; Kamil Marzec; Aleksandra Mokrzycka (International Journal of Innovative Technologies in Social Science, 2025)
Tirzepatide is a novel dual agonist of glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1 (GLP-1) receptors that offers promising therapeutic potential beyond glycemic control. Originally developed for the treatment of type 2 diabetes mellitus, tirzepatide has demonstrated a wide array of pleiotropic effects in clinical studies. These include significant reductions in body weight, improvements in lipid profiles, decreased blood pressure, and attenuation of hepatic steatosis. Emerging data also support its cardioprotective and nephroprotective roles, as well as efficacy in patients with heart failure with preserved ejection fraction (HFpEF). Furthermore, tirzepatide is currently under investigation for the treatment of obstructive sleep apnea and shows early promise in neuroprotection. This review summarizes the current evidence on the diverse biological actions of tirzepatide and discusses their potential clinical implications in the context of metabolic syndrome and associated comorbidities.Materials and methods: A review of the literature available in the PubMed database was performed, using the key words: “tirzepatide”, “obesity treatment”, “GIP”, “GLP-1”, “glucose-dependent insulinotropic polypeptide”, “glucagon-like peptide-1”.Conclusion: The clinical benefits of tirzepatide extend well beyond glucose lowering, encompassing a broad spectrum of metabolic, cardiovascular and renal effects. These pleiotropic actions position tirzepatide as a valuable pharmacological agent in the multifactorial management of type 2 diabetes, obesity and related conditions. Continued investigation into its mechanisms of action and therapeutic scope may further redefine its role in the treatment of complex metabolic disorders. Given the growing body of evidence, tirzepatide represents a paradigm shift toward integrated care for patients with metabolic syndrome and its systemic manifestations.